Widely accessible 3D printing technologies in chemistry, biochemistry and pharmaceutics: applications, materials and prospects. (December 2020) - Gordeev, E G; Ananikov, V P
Abstract: Representative examples of the application of 3D printing in organic synthesis, biochemistry, biotechnology, analytical chemistry, pharmaceutics and chemical education are considered. It is shown that additive technologies open up new prospects for the development of these fields of science. The characteristics of widely used 3D printing methods (fused deposition modelling and stereolithography) are discussed in the context of chemical applications. It is noted that the key feature of these methods is the wide accessibility of technologies and materials. The bibliography includes 498 references.